Indigenous genetic resources: A sustainable and environmentally friendly option for livestock production in areas at risk from trypanosomosis - D'Ieteren, G.D.M.; Kimani, K. (2000)
Trypanosomiasis is one of the major constraints on animal production in areas of Africa that have the greatest potential for significant increases in domestic livestock populations and livestock productivity. While various methods are being used by farmers to control the disease, major public efforts have been directed towards control of tsetse flies and on the use of trypanocidal drugs. Continent-wide fly eradication has recently been advocated as the ultimate solution needing public effort. Due to their nature, there are difficulties in sustaining the current methods of tsetse control. However, the efficacy of currently available trypanocidal drugs is also decreasing, due to drug resistance developing faster than generally thought. There is little hope that a conventional anti-parasite vaccine will be produced in the near future. Although less attention has been focussed on the use of naturally disease tolerant t livestock to cope with the disease, farmers in 19 out of 40 countries in the most humid parts of West and Central African countries affected by the disease are using these livestock as a major, if not only, option to cope with the problem in an economically sustainable and environmentally friendly way. There is increasing recognition that Africa possesses animal genetic resources probably unparalleled in any other continent. The natural innate resistance possessed by breeds of cattle such as the N'Dama and the West African shorthorn to trypanosomiasis and to several other important infectious diseases should be an increasingly important component of national and regional disease control programmes. Researchers are providing support for this environmentally healthy solution which has been demonstrated to be economically viable at both public and private levels.